Demonstrasi Pengujian Fitokimia Tumbuhan Air di Kabupaten Simalungun - Herna Febrianty Sianipar; Apriani Sijabat; Christa Voni Roulina Sinaga; Mardame Pangihutan Sinaga; Tambos Sianturi; Siti Imroatul Maslikah (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Purpose of this community service is to provides education on the benefit of aquatic plants for human health. In Simalungun, this service was provided with a socialization and questionnaire approach. Because aquatic plants include secondary metabolite chemicals that can treat diseases, the results of the counseling showed that the community did not understand the benefits of aquatic plants for human health. From the counseling, it was seen that the community has a very high level of passion and is increasingly aware of the benefits of aquatic plants for human health.